Determinación de hdl-colesterol y ldl-colesterol en personas adultas de ambos sexos, que acuden a la posta de salud de Buenos Aires sur del distrito de Víctor Larco, en octubre 2008” - Vigo Pesantes, Evelyn Adelaide (2009)
In the present study we determined the levels of HDL-c and LDL-c in adults of both sexes attending the health posts of the District of South Buenos - Víctor Larco in October 2008. The sample was 78 persons, whose data were collected through survey and informed consent was taken from a blood sample to determine the values of HDL-c and LDL-c by the enzymatic method. According to the values established by the American Heart Association found that 56.24% of people had higher values of HDL-c, of these, 90.9% were female and the male 9.1%, as to the age interval 14.1% who had higher values of HDL-c is between 36 - 45 years old, on the other hand, 43.6% of people have low levels of LDL-c, without any risk of coronary heart disease or atherosclerosis, 97% of them were females and 3% were males, but the values 1.28% higher